2020
DOI: 10.1111/his.14123
|View full text |Cite
|
Sign up to set email alerts
|

Somatic tumour testing establishes that bilateral DICER1‐associated ovarian Sertoli–Leydig cell tumours represent independent primary neoplasms

Abstract: Aims Sertoli–Leydig cell tumours (SLCTs) are rare ovarian neoplasms that are commonly associated with somatic or germline DICER1 mutations, especially when of the moderately or poorly differentiated type. A large majority are unilateral, but bilateral neoplasms have been reported, sometimes in the context of germline DICER1 mutations (DICER1 syndrome). It is currently unknown whether these represent independent neoplasms or metastasis from one ovary to the other and we aimed to elucidate this. Methods and resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The ages of our patients ranged from 4 to 16 years (median, 14 y), similar to the study from the European Cooperative Study Group on Pediatric Rare Tumors (EXPeRT) that showed a median age of 13.9 (range, 0.4 to 17.5) years in ovarian SLCTs of children and adolescents (n=44) 24 . SLCTs are almost always unilateral, and bilaterality may be associated with germline DICER1 mutation 25 . The study in ovarian SLCTs of children and adolescents from EXPeRT showed that 43 patients (43/44; 97.7%) had unilateral tumors and 1 patient (1/44; 2.3%) presented with a synchronous bilateral tumor 24 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The ages of our patients ranged from 4 to 16 years (median, 14 y), similar to the study from the European Cooperative Study Group on Pediatric Rare Tumors (EXPeRT) that showed a median age of 13.9 (range, 0.4 to 17.5) years in ovarian SLCTs of children and adolescents (n=44) 24 . SLCTs are almost always unilateral, and bilaterality may be associated with germline DICER1 mutation 25 . The study in ovarian SLCTs of children and adolescents from EXPeRT showed that 43 patients (43/44; 97.7%) had unilateral tumors and 1 patient (1/44; 2.3%) presented with a synchronous bilateral tumor 24 .…”
Section: Discussionsupporting
confidence: 75%
“…24 SLCTs are almost always unilateral, and bilaterality may be associated with germline DICER1 mutation. 25 The study in ovarian SLCTs of children and adolescents from EXPeRT showed that 43 patients (43/44; 97.7%) had unilateral tumors and 1 patient (1/44; 2.3%) presented with a synchronous bilateral tumor. 24 In our study, all of 8 SLCTs were confined to 1 ovary.…”
Section: Discussionmentioning
confidence: 96%
“…Two of our samples harbored a DICER1 hotspot mutation, which was the p. E1705K mutation. It was established by previous studies [12][13][14][15] that p. D1709N was the most common mutation hotspot in SLCTs, followed by p. E1813K. Other mutations included p. E1705K, p. D1709G, p. D1709V, p. G1809R, p. D1810Y, p. E1813Q, and p. E1813D.…”
Section: Discussionmentioning
confidence: 88%
“…While Apellaniz-Ruiz in their review showed that nearly all gynecologic ERMSs (except vaginal tumours) were DICER1 -associated, Doros et al detected DICER1 mutation in only 3.8% (2/52) cases of sporadic ERMS and the Children's oncology group cohort of pediatric rhabdomyosarcomas showedDICER1 germline mutation in 4.4%. 10,[17][18][19][20] DICER1 -associated central nervous system sarcomas also have a high association with rhabdomyosarcomatous differentiation. 8,21,22 Our CNS case mimicked mesenchymal chondrosarcoma, though it expressed ERMS markers.…”
Section: Discussionmentioning
confidence: 99%